Developing Learning Kit of Geometry for Vocational School Grade X Based on Multiple Intelligence Theory - Aep Sunendar; Ali Mahmudi (SEAMEO Regional Centre for QITEP in Mathematics, 2019)
This study aims to develop a learning kit of geometry for Indonesian vocational schools, grade X based on the multiple intelligence theory. This research and development used the 4D model suggested by Thiagarajan, Semmel and Semmel (1974) consisting of four stages that are: define, design, development, and disseminate. The data were analyzed by converting the actual scores obtained into a qualitative five category scale. The effectivity was analyzed by determining the percentage of students’ who completed a test and the percentage of students in each category as collected by the questionnaires. The Lesson Plan and worksheets were found to be valid. The results showed that the Lesson Plan and worksheet were practical based on the result of implementation, teacher’s assessment and students’ assessment. Furthermore, the Lesson Plan and worksheet were regarded as effective as reported by the students’ increasing achievement of spiritual attitudes, social attitudes, and knowledge competences. However, in terms of skill competences, the Lesson Plan and worksheet were not effective.